KEJADIAN ISPA PADA BALITA DI KELURAHAN PEMATANG KAPAU KOTA PEKANBARU - Nila Puspita Sari; Denai Wahyuni; Aszuna Dwi Krisna (Ensiklopedia of Journal, 2023)
Acute Respiratory Infection (ARI) is an acute infection involving the upper and lower respiratory tract organs caused by viruses, fungi and bacteria. The condition of the home environment that does not meet the requirements and smoking habits of family members in the house are the factors for the incidence of ARI among toddlers in Pematang Kapau Village, Pekanbaru City. The purpose of this study was to determine the incidence of ARI among children under five in Pematang Kapau Village, Pekanbaru City. This type of research is quantitative using a cross sectional design. Conducting interviews, observation and house measurements, namely house ventilation and house humidity with a total sample of 141 respondents using the total sampling technique. The subjects of this study were mothers of toddlers aged 13-59 months. The research was conducted in Pematang Kapau Village, Pekanbaru City in July - August 2020. Data analysis was carried out univariate and bivariate using the Chi Square test. The results of research it can be concluded that there are a relationship between the area of house ventilation Pvalue = 0.002 (α <0.05), house humidity Pvalue = 0.001 (α <0.05), occupancy density Pvalue = 0.002 (α < 0.05) and smoking habits of family members Value = 0.002 (α <0.05) with the incidence of ARI in toddlers in Pematang Kapau Village in 2020. The suggestions are to provide prevention and control for the community and can be used as a reference for knowing physical factors of the house and smoking habits of family members that cause ARI in toddlers.